Analysis of waste thermal energy from banana peels using decomposition process for heat generation - Mohamad Iskandar, Jobli; Diana Kertini, Monir; Khoo, Kian Peng (IEEE, 2011)
Decomposition of biomass due to bacterial activity results in the release of energy and warming of the mass. Therefore, the heat produced from the decomposition can be exploited effectively through a construction of a heat exchanger system. The working principle for this system is similar to that of ground source heat pumps. However, the system uses heat released from decaying biomass instead of geothermal heat from the ground. The main objective of this experimental work is to evaluate the potential of designing a heat pump system utilising the heat recovered from banana peels as a source of energy. Theheat exchanger system consists of pipes with a circulating medium (water) running through the piles of decaying biomass to extract heat released during the decomposition process. A heat pump could also be applied to the heat exchanger to increase its efficiency. The amount of energy extracted from the system is given by the temperature difference of circulating medium between the inlet and outlet pipe of the system. This system will analyse and evaluate the dependence of heat release rate on temperature. Results obtained during experimental testing are presented and discussed here. The rate of heat extraction from the compost will be determined and analysed throughout the system. Heat exchanger system constructed from banana peels managed to secure an estimated amount of 3 to 4 watt heat power per kilogram dry matter.